Iron Regulator Hepcidin Impairs Macrophage-Dependent Cardiac Repair After Injury. Issue 12 (19th March 2019) - Zlatanova, Ivana; Pinto, Cristina; Bonnin, Philippe; Mathieu, Jacques R.R.; Bakker, Wineke; Vilar, Jose; Lemitre, Mathilde; Voehringer, David; Vaulont, Sophie; Peyssonnaux, Carole; Silvestre, Jean-Sébastien
Abstract : Background: Defective systemic and local iron metabolism correlates with cardiac disorders. Hepcidin, a master iron sensor, actively tunes iron trafficking. We hypothesized that hepcidin could play a key role to locally regulate cardiac homeostasis after acute myocardial infarction. Methods: Cardiac repair was analyzed in mice harboring specific cardiomyocyte or myeloid cell deficiency of hepcidin and challenged with acute myocardial infarction. Results: We found that the expression of hepcidin was elevated after acute myocardial infarction and the specific deletion of hepcidin in cardiomyocytes failed to improve cardiac repair and function. However, transplantation of bone marrow–derived cells from hepcidin-deficient mice ( Hamp −/− ) or from mice with specific deletion of hepcidin in myeloid cells (LysM CRE/+ / Hamp f/f ) improved cardiac function. This effect was associated with a robust reduction in the infarct size and tissue fibrosis in addition to favoring cardiomyocyte renewal. Macrophages lacking hepcidin promoted cardiomyocyte proliferation in a prototypic model of apical resection–induced cardiac regeneration in neonatal mice. Interleukin (IL)–6 increased hepcidin levels in inflammatory macrophages. Hepcidin deficiency enhanced the number of CD45 + /CD11b + /F4/80 + /CD64 + /MHCII Low /chemokine (C–C motif) receptor 2 (CCR2) + inflammatory macrophages and fostered signal transducer and activator of transcription factor-3 (STAT3) phosphorylation, an instrumental step in the release of IL-4 and IL-13. The combined genetic suppression of hepcidin and IL-4/IL-13 in macrophages failed to improve cardiac function in both adult and neonatal injured hearts. Conclusions: Hepcidin refrains macrophage-induced cardiac repair and regeneration through modulation of IL-4/IL-13 pathways. Abstract : Supplemental Digital Content is available in the text.